Influence of diffusion on space-charge-limited current measurements in organic semiconductors - Kirchartz, Thomas (Beilstein Journal of Nanotechnology, 2013)
Numerical simulations of current–voltage curves in electron-only devices are used to discuss the influence of charged defects on the information derived from fitting space-charge-limited current models to the data. Charged, acceptor-like defects lead to barriers impeding the flow of electrons in electron-only devices and therefore lead to a reduced current that is similar to the situation where the device has a built-in voltage. This reduced current will lead to an underestimation of the mobilities and an overestimation of characteristic tail slopes if analytical equations are used to analyze the data. Correcting for the barrier created by the charged defects can, however, be a successful way to still be able to obtain reasonably accurate mobility values.
Keywords: current–voltage curves; electron-only device; drift–diffusion; mobility; simulation; traps